Biological assessment of the effects of toxic metals on plant biomass production - Michael, Patrick S (International Journal of Environment, 2014)
A significant environmental problem is the disturbance of acid sulfate soils which contain high amounts of sulfuric acid or have the potential to form it, resulting in pollution of the environment due to mobilization of toxic metals into soil and water systems. Reported in this study are two bioassay experiments carried out using wheat plants (Triticum sp.) to investigate the potential causes of a significant environmental problem experienced in a farmland. The results obtained show that availability of excessive amounts of Fe in the rhizosphere and formation of Fe-complex plagues, either acted as barriers to nutrient uptake or enhanced uptake of potentially toxic metals in excessive amounts; coupled with the presence of toxic levels of Al killed the vegetation on the farmland. DOI: http://dx.doi.org/10.3126/ije.v3i1.9942 International Journal of Environment Vol.3(1) 2014: 56-67